Motivation of Parents to Choose Religious Educational Institutions as Means of Child Education - Rasdiany, Apriana Nofriastuti; Putri, Viona Yolanda; Azizah, Dinda Dwi; Asril, Zainal; Albizar, Albizar (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2022)
Children's education is the responsibility of every parent; therefore parents must be able to provide the best quality education for their children, including choosing an educational institution, one of which is the State Madrasah Ibtidaiyyah. This study aims to analyze the motivation of parents to choose religious education institutions as a means of children's education. This study used a qualitative method with a case study approach, data sources were taken from fifteen informants through direct interviews using a set of interview protocols. All data were analyzed thematically using the Miles and Huberman technique. Overall, the study results show five main themes of parents' motivation to choose Madrasah Ibtidaiyaah Negeri as their child's educational institution. The five themes are: i) prioritizing religious learning and general learning, ii) emphasizing character education through religious activities iii) students are able to apply Islamic norms in everyday life, iv) complete infrastructure facilities in Madrasahs, and v) environmental atmosphere nice madrasa. The results of this study can be used as initial data for future researchers in studying parental motivation in the context of different issues.